2022
DOI: 10.1016/j.scs.2021.103397
|View full text |Cite
|
Sign up to set email alerts
|

CFD modeling of airborne pathogen transmission of COVID-19 in confined spaces under different ventilation strategies

Abstract: Airborne transmission is an important route of spread of viral diseases (e.g., COVID-19) inside the confined spaces. In this respect, computational fluid dynamics (CFD) emerged as a reliable and fast tool to understand the complex flow patterns in such spaces. Most of the recent studies, nonetheless, focused on the spatial distribution of airborne pathogens to identify the infection probability without considering the exposure time. This research proposes a framework to evaluate the infection probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 38 publications
(45 reference statements)
0
34
0
Order By: Relevance
“…They found that when the supply register is at the bottom, and the return register is at the top, it is the best form to reduce the concentration of pathogenic particles. Motamedi et al [11] proposed a framework to assess the infection probability under different ventilation strategies. Kotb et al [12] studied how the virus spreads through coughing and sneezing in an airplane cabin and concluded that sneezing is more contagious than coughing, because sneezing droplets travel longer distances.…”
Section: Introductionmentioning
confidence: 99%
“…They found that when the supply register is at the bottom, and the return register is at the top, it is the best form to reduce the concentration of pathogenic particles. Motamedi et al [11] proposed a framework to assess the infection probability under different ventilation strategies. Kotb et al [12] studied how the virus spreads through coughing and sneezing in an airplane cabin and concluded that sneezing is more contagious than coughing, because sneezing droplets travel longer distances.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving ventilation efficiency is critical in the face of large ventilation demand [21]. From the perspective of airflow pattern, the development of efficient ventilation systems and ventilation modes can contribute to mitigating the transmission of infectious disease and improving the energy saving efficiency [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, risk assessment in relation to human exposure to infectious droplets play a vital role in the early stage of the disease transmission investigation (Nicas et al, 2005). Due to the human exposure risk is closely linked to the occupants exposed to pathogen-bearing droplets for a given time period that is influenced by various affecting factors (e.g., ventilation), it could be a good reference to reflect the effectiveness of the implemented measures (Motamedi et al, 2022). Recently, with the increasing demand for conducting a robust and fast evaluation of human indoor exposure risks, the use of CFD-based simulation is becoming more popular as it can cost-effectively assess the exposure risk by visualising detailed droplet trajectories (Peng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%